WORDY CARD FOR AN INNOVATIVE TEACHING METHOD FOR LEARNING ENGLISH - Ni Putu Dilia Dewi; Dian Rahmani Putri; Dadang Hermawan (Indonesian Journal of Educational Development (IJED), 2023)
The foundation of learning a new language is vocabulary. Teaching vocabulary has been done in conjunction with teaching other language skills. Due to their little language knowledge, students continue to have trouble speaking. Meanwhile, senior high school students must get ready for either further education or the realm of industrial job. To address this issue, innovative teaching strategies in English are required. In this study, How Wordy card games can be used as innovative teaching tools to help kids in senior high school develop their vocabulary. Students in classes X, XI, and XII at SMK TI Bali Global Denpasar and SMK Negeri 2 Denpasar are the data sources. Techniques for gathering data that involve both direct observation and interviews. Data are analyzed using a descriptive qualitative approach, and they are then presented in a narrative format. The R&D procedures were modified from Borg and Gall's (1983) ten-cycle method of creating wordy cards. This study created a special card game that can be played at all educational levels and is particularly beneficial to teachers in their vocabulary instruction.